Superhydrophobic light-driven actuator based on self-densified wood film with a sandwich-like structure. (22nd March 2022) - Chen, Junqing; Zhu, Zhaodong; Zhang, Hui; Fu, Shiyu
Abstract: Response actuators based on different stimuli such as light, humidity and temperature have attracted extensive attention due to their advantages in various environments. In this work, a facile top-down strategy is proposed to prepare a light stimuli-responsive self-densified wood film. We constructed a sandwich-like structure by in-situ co-precipitation of Fe3 O4, spraying CNT, self-densification and chemical vapor deposition methyltrimethoxysilane (MTMS) on TEMPO-oxidized delignified wood. The CNT/Fe3 O4 /MTMS wood film exhibits excellent strength (56 Mpa along the fiber direction), superhydrophobicity (water contact angle of 151°) and photothermal conversion performance. The Fe3 O4 in the film plays a good role of photothermal conversion, which makes the photothermal conversion effect of the film double that of the wood film sprayed only with CNT. Under near-infrared (NIR) light irradiation and focused sunlight, the film exhibits a light-driven response of linear motion on the water surface. Based on the excellent electrical conductivity and light stimulus responsiveness of the film under NIR irradiation, an electrical switch is successfully designed and can be remotely controlled. Moreover, the film is easy to recycle due to magnetism, it is also very stable under moisture environment due to the protection of the superhydrophobic coating and the dense structure created by self-densification. Graphical abstract: Image 1 Highlights: A light-stimulus-responsive wood film with a sandwich structure is fabricated for light-driven actuators. The material adopts a simple film forming method that is self-densification. Fe3 O4 not only enhances the photothermal conversion, but also makes the film recyclable through magnetism. The material exhibits excellent superhydrophobicity, photothermal conversion capability and stability.